Prevalence of headache in children and adolescents: a literature review - Filho, Otavio Pereira da Silva; Pinheiro, Giulia Rebouças; Nunes, Melyssa Maria Fernandes da Rocha; Soares, Ana Clara Mendes; Azevedo, Marina Pinheiro Uchoa; Lousada, Lívio Martins; Coutinho, Isadora Pinheiro; Moura, Lucas Eliel Beserra (Headache Medicine, 2023)
Full abstract in PDF.